Tectono‐sedimentary evolution of the Tertiary Piedmont Basin (NW Italy) within the Oligo–Miocene central Mediterranean geodynamics. Issue 3 (7th June 2013) - Maino, Matteo; Decarlis, Alessandro; Felletti, Fabrizio; Seno, Silvio
Abstract [1] We analyze the tectono‐sedimentary and thermochronometric constraints of the Tertiary Piedmont Basin (TPB) and its adjoining orogen, the Ligurian Alps, providing new insights on the basin evolution in response to a changing geodynamic setting. The geometry of the post‐metamorphic faults of the Ligurian belt as well as the fault network that controlled the Oligo–Miocene TPB deposition has been characterized through a detailed structural analysis. Three main faulting stages have been distinguished and dated thanks to the relationships among faults and basin stratigraphy and thermochronometric data. The first stage (F1, Rupelian–Early Chattian) is related to the development of extensional NNW‐directed faults, which controlled the exhumation of the orogen and the deposition of nearshore clastics. During the Late Chattian, the basin drowning is marked by mudstones and turbidites, which deposition was influenced by the second faulting stage (F2). This phase was mainly characterized by NE‐ to ENE‐striking faults developed within a transtensional zone. Since the Miocene, the whole area was dominated by transpressive tectonics. The sedimentation was represented by a condensed succession followed by a very thick, turbiditic complex. At the regional scale, this succession of events reflects the major geodynamic reorganization in the central Mediterranean region during the Oligo–Miocene times, induced by the late‐collisional processes of the Alps, by the eastward migration of the Apennines subduction and by the opening of extensional basins (i. e., the Liguro–Provençal Ocean).